Keikutsertaan Keikutsertaan dalam kelas antenatal Dapat menurunkan intensitas nyeri persalinan Kala 1 fase aktif - Lenny Nainggolan (Poltekkes Kemenkes Medan, 2021)
The antenatal classes are means of learning activity for pregnant woman, together in a group which aimed to increase their knowledge and skills. During the labor process, there are various problems that may occur in the mother, one of which is labor pain. Efforts that can be made to reduce the pain problems are through the implementation of antenatal classes. The purpose of this study was to determine the relationship of antenatal classes and the intensity of labor pain during the active phase of labor. This is an observasional analytic study with cohort design in 33 mothers who attended the antenatal classes. The sampling tehnique that used is consecutive sampling and the data were analyzed by chi-square. As the results of data analysis on the relationship between the antenatal class and the intensity of labor pain during the first stage of active phase, the value of p = 0.000. The P value < 0.05. The results of data analysis obtained that there was a relationship between the antenatal class and the intensity of the labor pain during the first stage of the active phase. Midwives are expected to be able to increase the quality of antenatal classes and can attract the interest of the community, especially pregnant woman to actively participate antenatal classes.